Movimentos sociais do campo, práticas educativas e (re)configurações do território: leituras a partir da luta do povo de Alagamar - Neves, Gildivan Francisco das (2022)
The Luta do Povo de Alagamar (Struggle of the People of Alagamar) was a social movement that took place in the 1970s, in Alagamar, located between the municipalities of Itabaiana and Salgado de São Félix, in Paraíba, and is part of a scenario of struggles and resistance in the countryside, which has contributed to (re)configure it. In this way, we list the (re)configurations of the territory of Alagamar as an object of study, based on the educational practices built by rural workers in the participation in the social movement of this event. As a problem: in what way, the educational practices built by rural workers, through their participation in the Luta do Povo de Alagamar, (Struggle of the People of Alagamar) contributed to the triggering of (re)configurations in the territory, from the social movement? In view of this, we list as a general objective to analyze how the educational practices built by rural workers in the Alagamar People's Fight contributed to the (re)configuration of the territory in which it was carried out. As specific objectives, we highlight: a) To contextualize the territory of Alagamar, taking as a reference the social movement in this event; b) Discuss the different proposals for solutions to the situation of exclusion experienced in Alagamar, in the context of the social movement, as echoes of different interpretations of the territory; c) Understand how the social movement and the educational practices built on it contributed to the construction of new readings for the territory of Alagamar; and, d) Gather sources for the local history, contributing to the treatment with the memory of the social movement, in the scope of rural education, in the territory in which it was carried out. We present as a thesis the following argument: through participation in the Luta do Povo de Alagamar (Struggle of the People of Alagamar), rural workers built educational practices that contributed to the construction of new readings and (re)configurations for the territory in which it took place. We start from the field of Popular Education that allowed us to enter the local history of the territory in which the social movement was carried out, visualizing the territory and its memories, to the South. This is a qualitative research, based on documentary research, having as sources newspapers, booklet, pastoral letters written by D José Maria Pires, Informativo Arquidiocesano no 83 of 1980, photographs, analyzed considering the provisions of Bacellar (2008) and Le Goff (2012) on dealing with documents. From these authors, we built a file that contributed to the cataloging and analysis process and resulted in the construction of a product that we call Source Catalog: Luta do Povo de Alagamar. We realized that in the context of the social movement, there were divergent readings for the territory, which affected the resistance made by rural workers, in the search for expropriation and permanence in the locality and in the actions of the new owners, with a view to expelling the residents of Alagamar. This referred to a space for the construction of educational practices, from which learning was generated, which enabled rural workers to build a struggle that continues, facing the understanding that the measures adopted by the state government and the federal government did not solve the problem. and, thus, interfering in the (re)configuration and uses of the territory. This thesis, through the construction of the catalogue, contributes to dealing with local history, in rural education in Alagamar, while presenting sources that allow building dialogues with the territory, its memories and stories.